Politically connected firms and external audit fees in Malaysia: An internal audit function perspective / Norziaton Ismail Khan, S. Susela Devi and Chan Wai Meng - Ismail Khan, Norziaton; S., Susela Devi; Chan, Wai Meng (Accounting Research Institute (ARI) & Faculty of Accountancy, 2015)
This study extends the literature on the role of internal audit function in corporate governance and auditing by testing two hypotheses. The first hypothesis predicts that the association between internal audit objectivity and external audit fees is stronger after the implementation of the Bursa Malaysia Listing Requirements 2008 implementation for politically connected firms than for non-politically connected firms. The second hypothesis predicts that the association between internal audit work performance and external audit fees is stronger after the implementation of the Bursa Malaysia Listing Requirements 2008 for politically connected firms than for non-politically connected firms. Using data from 945 firm-year observations for the years 2005 to 2009, internal audit function attributes, namely y objectivity and work performance, and external audit fees are stronger post-2008. This finding suggests that politically connected firms are more likely to use a greater level of internal audit function and are more willing to pay for a higher quality of external audit work, thus acquiring higher external audit fees.